2008
DOI: 10.4161/cc.7.10.5826
|View full text |Cite
|
Sign up to set email alerts
|

DNA Replication, cell cycle progression and the targeted gene repair reaction

Abstract: Single-stranded oligonucleotides (ssODNs) can direct base changes in mammalian cells and influence changes in phenotype. The mechanism by which ssODNs alters the sequence is being revealed by studies carried out in model systems. In the long run, this information will provide the basis for clinical protocols designed to target genetic diseases. It is now clear that DNA replication plays an important part in the gene repair reaction. Here, we examine gene repair as a function of the amount of cells passing thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
45
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3
1

Relationship

4
6

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 44 publications
6
45
0
Order By: Relevance
“…The three NT-ssODNs are of identical sequence through 40 bases but vary in length from 40 to 72 to 100 nucleotides respectively. This system is well established as a model for analyzing the mechanism of gene editing in human cells [9] [29][30]. In most applications, 72NT ssODN has been used in optimization studies for delivery and the response of cell and genomic DNA in the gene editing reaction [20].…”
Section: Resultsmentioning
confidence: 99%
“…The three NT-ssODNs are of identical sequence through 40 bases but vary in length from 40 to 72 to 100 nucleotides respectively. This system is well established as a model for analyzing the mechanism of gene editing in human cells [9] [29][30]. In most applications, 72NT ssODN has been used in optimization studies for delivery and the response of cell and genomic DNA in the gene editing reaction [20].…”
Section: Resultsmentioning
confidence: 99%
“…Over the course of the last 15 years we and others have established the mechanism and regulation of short oligo induced gene editing [24,10,11,34]. More recent studies have shown that oligonucleotides of length between 49 and 72 bases respectively can direct single base repair as the sole agent of the gene editing reaction or in combination with both TALENs and CRISPR/Cas9 [33,35].…”
Section: Discussionmentioning
confidence: 99%
“…Studies on oligonucleotide ssODNs and cell cycle indicated that gene modification frequencies varied considerably between the various cell cycle phases, in particular late S-phase was shown to be the most amenable for gene repair [20], probably due to increased activity of replication forks and to a more favorable chromatin conformation. Transfecting SDFs into cells synchronized in different cell cycle phases, we noticed that replacement efficiencies were highest in vinblastine-enriched G 2 /M-phase cells.…”
Section: Discussionmentioning
confidence: 99%